2014
DOI: 10.1021/om500156q
|View full text |Cite
|
Sign up to set email alerts
|

A Broadly Applicable Strategy for Entry into Homogeneous Nickel(0) Catalysts from Air-Stable Nickel(II) Complexes

Abstract: A series of air-stable nickel complexes of the form L2Ni(aryl) X (L = monodentate phosphine, X = Cl, Br) and LNi(aryl)X (L = bis-phosphine) have been synthesized and are presented as a library of precatalysts suitable for a wide variety of nickel-catalyzed transformations. These complexes are easily synthesized from low-cost NiCl2·6H2O or NiBr2·3H2O and the desired ligand followed by addition of 1 equiv of Grignard reagent. A selection of these complexes were characterized by single-crystal X-ray diffraction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
174
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(181 citation statements)
references
References 55 publications
5
174
0
Order By: Relevance
“…136) (FIG. 5a), they are often preferred to dihalide precatalysts because they are generally bench-stable, are activated by milder nucleophiles, have greater solubility in many solvents and can be used for ligand screening 137140 .…”
Section: Ni-based Precatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…136) (FIG. 5a), they are often preferred to dihalide precatalysts because they are generally bench-stable, are activated by milder nucleophiles, have greater solubility in many solvents and can be used for ligand screening 137140 .…”
Section: Ni-based Precatalystsmentioning
confidence: 99%
“…By far the most common Ni(0) precatalyst is [Ni(COD) 2 ], which is typically mixed with the appropriate ligand to generate a more electron-rich complex in situ . However, [Ni(COD) 2 ] is relatively expensive, thermally unstable and air-sensitive 13,136,153 . With respect to the latter, it has recently been shown that [Ni(COD) 2 ] can be encapsulated in paraffin capsules so that it can be used under aerobic conditions; the problems associated with its cost and thermal stability remain 164 .…”
Section: Ni-based Precatalystsmentioning
confidence: 99%
“…According to the five important points required, as set out by Matsubara et al [24] when designing a multi-functional nickel catalyst, the series [CpNiBr(NHC)] (1 -9) conforms to the requirements. This is because complexes 1 -9 (i) are prepared in a facile fashion, (ii) are thermally and relatively air and moisture stable, (iii) easily form a coordinatively unsaturated site with mild bases, (iv) possess electron-donating ligands to stabilise the unsaturated site which accelerates the oxidative addition process, and (v) exhibit a range of steric substituents on the NHC ligand to enhance the reductive elimination reaction [12,25]. …”
Section: Suzuki-miyaura Coupling Activitymentioning
confidence: 99%
“…In the plethora of C-C coupling reactions, the Suzuki-Miyaura reaction has become one of the most studied for catalytic applications due to its tolerance of functional groups and low toxicity of its by-products [4d, 15,19,20a,25,26]. Furthermore, [CpNiX(NHC)] (X = halide) and related systems have provided equal or improved catalytic activity in some C-C coupling reactions when compared to the traditional Pd catalysts [10,12,20,25,27]. In spite of this, the bromo complexes in the series of [CpNiBr(NHC)] compounds reported are few when compared to their chloro-and iodo-analogues [10,19].…”
Section: Introductionmentioning
confidence: 99%
“…These air-stable Ni σ-aryl precatalysts were further explored in subsequent studies and can be prepared from numerous ligands. 44 …”
Section: Alkenes As Nucleophilesmentioning
confidence: 99%